Shear Wave Elastography in the Evaluation of the Kidneys in Pediatric Patients with Unilateral Vesicoureteral Reflux. (19th July 2018) - Kalyoncu Ucar, Ayse; Cicek, Rumeysa Yasemin; Alis, Deniz; Akbas, Serkan; Arioz Habibi, Hatice; Arslan, Mine Usta; Eral, Gokalp; Suleyman, Ayse; Caliskan, Salim; Adaletli, Ibrahim
Abstract : Objectives: To evaluate the ability of shear wave elastography (SWE) to detect renal parenchymal scar formation in patients with vesicoureteral reflux. Methods: We prospectively evaluated 49 patients with unilateral grade 2 or higher‐degree VUR. All patients underwent dimercaptosuccinic acid (DMSA) scintigraphy for evaluation of the renal parenchymal scar. After the DMSA scan, 2 radiologists, who were blinded to clinical data and each other's measurements, evaluated the kidneys of the patients using SWE. The kidneys were divided into 3 parts: upper pole, middle region, and lower pole, and 3 regions of interest were placed to each part. Shear wave velocity (SWV) values were calculated using meters per second as a unit and recorded for each region. Afterward, SWV values were compared to DMSA results. Results: There was no significant difference between the observers' mean SWV values of kidneys with VUR without scar formation (mean ± SD, 2.11 ± 0.06 and 2.09 ± 0.05 m/s) and the contralateral normal kidney SVW values (2.11 ± 0.06 and 2.10 ± 0.05 m/s; P  = .936 and .724, respectively). We observed a significant difference between the mean SWV values of the kidneys with VUR accompanied by scar formation (2.28 ± 0.10 and 2.27 ± 0.11 m/s) and the mean SWV values of the contralateral normal kidneys (2.09 ± 0.05 and 2.10 ± 0.04 m/s; P  < .001 for both observers). Conclusions: Shear wave elastography could detect scar tissue in kidneys; however, the variability of the stiffness due to the kidney's complex structure, and variations in blood perfusion and the glomerular filtration rate of the kidney might limit the use of SWE in current clinical diagnostic algorithms for VUR.